1996
DOI: 10.1111/j.0022-3646.1996.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE THAT MICROCYSTIN IS A THIO‐TEMPLATE PRODUCT1

Abstract: The hepatotoxic cyclic heptapeptide toxins of cyanobacteria, collectively termed microcystins, are potent inhibitors of protein phosphatases PP1 and PP2A. The structure of microcystins resembles small, cyclic peptide secondary metabolites from fungi and eubacteria. Many of these metabolites are manufactured via a nonribosomal thio‐template mechanism. We submit evidence that microcystin is synthesized by a similar mechanism. The organism used in this study was Microcystis aeruginosa PCC7820. Using the tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…However, in the following 20 years, very few studies have been carried out to confirm these findings. It has been reported that microcystin was synthesized in vivo by mcy genes in some cyanobacterial genera, including Microcystis and Anabaena (Arment and Carmichael, 1996;Dittman et al, 1997), and mcyB gene was commonly used as an important indicator of toxin-producing ability for toxic cyanobacteria (Kurmayer et al, 2003). For example, Kurmayer and his colleagues determined the presence of mcy genes in different colonies of Microcystis blooms from a number of freshwater lakes, and found the mcyB gene in most of the M. aeruginosa colonies (>73%) but only in <16% of the M. ichthyoblabe colonies, whereas not in Microcystis wesenbergii colonies (Kurmayer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the following 20 years, very few studies have been carried out to confirm these findings. It has been reported that microcystin was synthesized in vivo by mcy genes in some cyanobacterial genera, including Microcystis and Anabaena (Arment and Carmichael, 1996;Dittman et al, 1997), and mcyB gene was commonly used as an important indicator of toxin-producing ability for toxic cyanobacteria (Kurmayer et al, 2003). For example, Kurmayer and his colleagues determined the presence of mcy genes in different colonies of Microcystis blooms from a number of freshwater lakes, and found the mcyB gene in most of the M. aeruginosa colonies (>73%) but only in <16% of the M. ichthyoblabe colonies, whereas not in Microcystis wesenbergii colonies (Kurmayer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Microcystin is produced nonribosomally by the microcystin synthetase enzyme complex via a thio-template mechanism (2). Nonribosomal peptide synthetase genes consist of modules that are built up of domains, and each module activates one amino acid, which is incorporated into the growing peptide chain in the order in which the modules are arranged.…”
mentioning
confidence: 99%
“…Microcystin is a hepatotoxic heptapeptide produced by several species of the genera Microcystis, Anabaena, Nostoc, and Oscillatoria. More than 65 structural isoforms of microcystins with various toxicities have been identified having the common structure cyclo(Adda-D-Glu-Mdha-D-Ala-L-X-D-MeAsp-L-Z), where X and Z are variable L amino acids, Adda is 3-amino-9-methoxy-2,6,8,-trimethyl-10-phenyl-4,6-decadienoic acid, D-MeAsp is 3-methylaspartic acid, and Mdha is N-methyldehydroalanine (27, 31).Microcystin is synthesized nonribosomally via a mixed polyketide synthase/nonribosomal peptide synthetase system called microcystin synthetase (2,12,23). Recently, the gene cluster encoding the microcystin synthetase complex has been identified and sequenced (25,34).…”
mentioning
confidence: 99%
“…Microcystin is synthesized nonribosomally via a mixed polyketide synthase/nonribosomal peptide synthetase system called microcystin synthetase (2,12,23). Recently, the gene cluster encoding the microcystin synthetase complex has been identified and sequenced (25,34).…”
mentioning
confidence: 99%